PEMASANGAN INSTALASI LISTRIK, PENCAHAYAAN DAN AIR BERSIH DI PURA RIJASA DESA BAHA, MENGWI - Made Rasta; I G.K. Abasana; I N. Suamir; P.W. Sunu; IW A Subagia; I K Widana (Bhakti Persada Jurnal Aplikasi IPTEKS, 2018)
Temple as a holy place of Hinduism in Bali inherited by the ancestors needs to be preserved. Temple as a means of worshiping God has a very broad dimension, in which there are various kinds of natural forces that can lead us to safety and happiness in this life. Temples that have old age due to the influence of time, are naturally damaged. In such conditions, the people are obliged to make improvements. The development carried out should continue to maintain its original function for its sustainability. The restoration carried out by the funding community was supported by the assistance of the Badung Regency Government and the descendants of the people and donations from donors. The main problem of the people is the limited availability of funds needed to repair the temple. Another thing that is urgently needed by the people is the availability of lighting and clean water. The purpose of this service is the availability of lighting and clean water in the temple to support temple activities. Religious ceremonies are essentially not only religious dimensions, but also social, artistic, economic, management and other dimensions. Through religious ceremonies, it can be fostered harmony between fellow human beings, families, one village with another village. Religious ceremonies also train people to be able to organize and are management exercises in regulating the course of the ceremony. Through religious ceremonies, ethics and aesthetics are also fostered. Religious ceremonies are very potential motivators to preserve or develop cultural arts, both the sacred and the profane. Even religious ceremonies are one of the attractions of tourism and can support human life. All religious cultures in the form of religious ceremonies are human endeavors to draw closer to Ida Sang Hyang Widi wasa to realize lasting peace and happiness. Balinese culture actually upholds the values of balance and harmonization, reflected in the teachings of Tri Hita Karana (three causes of welfare). If humans are able to maintain a balanced and harmonious relationship with these three aspects, welfare will be realized. Construction of temples complete with facilities and infrastructure, is expected to provide broad benefits for the community in developing tourism in Badung and Baha especially. Increasing the quality of the people, both as individual beings and as social beings. Community welfare will indirectly increase through economic performance and changes in the economic structure generated by the development of tourism.